Modeling of Cover Concrete Cracking Due to Uniform Corrosion of Reinforcement - Shakib, Sheikh; Morshed, Abu Zakir (Journal of Engineering Science, 2021)
Cracking of cover concrete due to the corrosion of reinforcing steel is one of the main causes of deterioration in Reinforced Concrete (RC) structures. An outbound stress is developed in concrete surrounding the reinforcing steels due to the expansive corrosion products of reinforcement leading to cracking of the concrete cover. In this paper, the cracking pressure was simulated through a finite element modeling. The effect of geometrical and material parameters, i.e. concrete cover thickness, bar diameter, and concrete tensile strength, on the cracking pressure was also investigated. Abaqus 6.14 was used as modeling platform. The cracking pressure was found to dependent on the cover thickness and tensile strength of concrete. A higher pressure was required to initiate crack for a higher cover thicknesses and tensile strength. The cracking pressure was decreased with the increase in bar diameter. Finally the crack initiation and propagation has been simulated successfully for different arrangements of reinforcements. Journal of Engineering Science 12(1), 2021, 43-49